Acquisition of the course profile and pre-competition race analysis of cross-country skiing in the Peyongchang Winter Olympic Games: - Yanaka, T.; Nakazato, K.; Fujita, Z.; Ishige, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
Cross-country skiers perform over a long distance using poles and skis. Physical fitness, in terms of factors such as VO2max and muscle strength, skiing technique and race strategy are important for winning competitions. To plan the race strategy, investigations of the course profile and race analysis are needed. The purposes of this study were to investigate cross-country skiing course profiles which were planned for the Winter Olympic Games at Peyongchang, and to analyze the men`s 15km+15km World Cup skiathlon race (SA) as a pre-competition event. A cross-country skier followed the classical and skating courses using a GNSS (Global Navigation Satellite System) antenna. The antenna instantly measured the latitude, longitude and height of the skier on the courses. The coordinate values on a plane were calculated from latitude and longitude, after the inclination was then calculated from the coordinate values and height every 10 m. The overall finish time and transit time at 24 points for 12 skiers in SA were retrieved from the Official Home Page of the International Ski Federation (FIS), and the segment times among the various points were calculated. Three segment times formed a lap, and each segment speed was calculated by dividing the segment distance by the segment time. For the classical course profile, the distance was 3819 m and the maximum inclination was 18.6%. In contrast, for the skating course, the distance was 3777 m and the maximum inclination was 20.6%. No correlation was found between the overall finish time and the segment times for the classical course. This result was attributable to small variations in the lap times for the classical course because of the skiers` use strategy, checking among competitors, and the mass-start. On the other hand, positive correlations were found between the overall finish time and the segment times on skating. In skating, the segment speeds from the final phase of the 2nd lap to the middle phase of the 3rd lap indicated deceleration relative to the 1st lap. These results suggest that gliding on a skating course in a short time is important for shortening the overall finish-time. Especially, it is important to minimize the deceleration of the 2nd and 3rd lap segment speed. The race pattern for the Olympic Games was similar to that of pre-competition, except for the time taken. These results indicate that pre-competition race analysis is useful for devising a strategy for target competition.